Moderating role of job control and coping strategies in the relationship between emotional job demands and burnout among health workers - Raissa Safridha Putri; Tulus Budi Sulistyo Radikun (KONSELOR, 2023)
Health workers are jobs that have a heavy burden. Long and uncertainty of working hours, patients with various characteristics with various diseases causing health workers to tend to have high levels of burnout. The purpose of this study is to aim to see the role of job control and coping strategies as a moderator in the relationship between emotional work demands and burnout. This research is a cross-sectional quantitative study which has a sample of 142 health workers. This study uses instruments from Oldenburg Burnout Inventory, Copenhagen Psychosocial Questionnaire II (COPSOQ II), Copenhagen Psychosocial Questionnaire and Brief COPE Inventory (Coping Orientation to Problems Experienced). Data processing uses process macro moderation analysis by Andrew F. Hayes through the SPSS Program. The results of the study show there are moderation effects of job control and coping strategies on emotional job demands and different dimensions of burnout. Job control as job resources moderates emotional job demands and the exhaustion dimension of burnout. While coping strategies as personal resources between emotional job demands and the burnout dimension of disengagement. Health workers can use their job control to overcome the emotional work demands experienced by health workers. Other than that, health workers can also be given activities or programs that can improve their coping skills, either those that focus on behavior or those that focus on emotions. This study might be implicating on health workers’s well-being from the findings, that job resources and personal resources could decrease the burnout level on health workers.